SUPERVISOR AS A CHANGE AGENT - Qamar, Khadija (Pakistan Journal of Physiology, 2018)
Interestingly the only constant we always come across is change. The 'change supervisor’s capabilities' have a major role in victory of the program, and on the extent of probable unwanted side-effects. It is necessary to win the support and commitment of the trainees. This acceptance depends extensively on high competency as well as soft skills, including communication skills, the capability to appreciate and to take into thought the views and suspicions of others. The role of a supervisor is to provide directions and motivation, and as a final step be able to implement plans. By increasing the urgency people start telling each other ‘let’s go, we need to change things’. They start building the guiding team. Now this group is powerful enough to guide a big change. The guiding team develops the right vision and strategy for the change effort. People begin to buy in the change which is reflected in their behaviors. Through empowered action, more learners feel able to act and do act on the vision. Momentum builds up as trainees try to fulfill the vision, while fewer and fewer resist change. Supervisors make wave after wave of changes until the vision is fulfilled. The new and winning behavior continues despite the pull of tradition perspectives. The ‘gravitational pull’ of conservative approaches is huge and proportionate but persistent force is required to break the barriers. The proportionate force cannot be generated without developing ‘muscles’ which is essential for the supervisors to act as change agents. This translates into a change that is firm and constant. Pak J Physiol 2018;14(2):1-2